Modeling Knowledge-Based Systems Using GFP-Nets - Suraj, Zbigniew (International Conference on Control, Decision and Information Technologies (Online), 2023)
The paper attempts to answer the question of whether there are, and if so, what, relationships between the selected properties of generalized fuzzy Petri nets and the features expected by designers of knowledge-based systems models they construct. The search for such relationships is carried out in the area of selected structural and dynamic properties, methods of marking changes and operating modes of such a net class and their optimized versions. Looking for the desired features of the designed models, the subject of research is their quality, efficiency, numerical stability and determinism. The research trend proposed in this work seems to fall within the scope of challenges presented in the review article on the state of research in the field of fuzzy Petri net theory and applications, developed by the authors Zhou & Zain and published in "Artificial Intelligence Review", 45, 405-446, 2016.